2014
DOI: 10.1371/journal.pone.0097870
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Runaway into an Avoidance Area in a Swarm of Soldier Crabs

Abstract: Emergent behavior that arises from a mass effect is one of the most striking aspects of collective animal groups. Investigating such behavior would be important in order to understand how individuals interact with their neighbors. Although there are many experiments that have used collective animals to investigate social learning or conflict between individuals and society such as that between a fish and a school, reports on mass effects are rare. In this study, we show that a swarm of soldier crabs could spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Such behaviors are made possible through communication (e.g. quorum sensing [50]) and synchronization between the different elements (cells) of the system, only when a critical number (or density) of individuals in the population is reached [51][52][53]. In such cases, the LLN and CLT may not likely hold, as the average behavior of individual cells is expected to be different from the behavior of the whole population.…”
Section: Resultsmentioning
confidence: 99%
“…Such behaviors are made possible through communication (e.g. quorum sensing [50]) and synchronization between the different elements (cells) of the system, only when a critical number (or density) of individuals in the population is reached [51][52][53]. In such cases, the LLN and CLT may not likely hold, as the average behavior of individual cells is expected to be different from the behavior of the whole population.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we show a local interaction named by mutual anticipation that is inspired the behavior of a swarm of soldier crabs3132333435. We previously proposed a model based both on the alignment and the mutual anticipation with asynchronous position updating3637.…”
mentioning
confidence: 80%
“…We found that this model of a swarm is more robust against external perturbations than previously considered models34. Moreover, we revealed that an emergent behavior of the soldier crabs could be explained by mutual anticipation31. In addition, we showed that a robust mobile swarm without collective order could be simulated using only on mutual anticipation without velocity matching and the randomly modified principal vector35.…”
mentioning
confidence: 87%
“…The swarm of the species has inherent noise that is individuals' different velocities in maintaining a densely and directed swarm [12]. Such an inherent noise has been found not only in the swarming of soldier crabs but also in other animal groups (e.g., [13,14]).…”
Section: Resultsmentioning
confidence: 99%